PENGARUH PELATIHAN DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PT. MUSTIKA RATU TBK, CIRACAS JAKARTA TIMUR - Aninda Putri Dewantari; Edy Sanusi Silitonga (Jurnal Ekonomi dan Industri, 2021)
The purpose of this study was to determine the training and communication on the performance of employees of PT. Mustika Ratu Tbk Ciracas, East Jakarta. This research is included in the category of causal associative research using a quantitative approach. The population in this study were all employees of PT. Mustika Ratu Tbk Ciracas, East Jakarta. The sampling technique is probability sampling using proportionate stratified random sampling. The research was conducted by distributing questionnaires to respondents, while the research method used simple and multiple linear regression analysis. The results of this study obtained data showing that either partially or simultaneously training and communication have a significant effect on the performance of employees of PT. Mustika Ratu Tbk Ciracas, East Jakarta.